Gall-inducing arthropods in a Neotropical savanna area in the EPA of Rio Pandeiros (Bonito de Minas, MG, Brazil): effects of plant species richness and super-host abundance - Araújo, Walter Santos de; Costa, Kelly Christie dos Santos; Silveira, Luana Teixeira; Freitas, Érica Vanessa Durães de; Nunes, Yule Roberta Ferreira; Azevedo, Islaine Franciely Pinheiro de (Papéis Avulsos de Zoologia, 2020)
Several plant-related factors can influence the diversity of gall-inducing species communities. In the present study we performed an inventory of gall-inducing arthropods and we tested if the plant species richness and the abundance of super-host plants (Copaifera oblongifolia) influenced positively in the diversity of gall-inducing arthropod species. The study was realized in an area of Neotropical savanna (cerrado sensu stricto) in the Environmental Protection Area (EPA) of Rio Pandeiros, Minas Gerais, Brazil. Host-plant species and gall-inducing arthropods were sampled in 18 10 × 10 m plots distributed in the vegetation. In total we found 40 arthropod gall morphotypes, distributed on 17 botanical families and 29 plant species. Cecidomyiidae (Diptera) induced the most arthropod galls (85%), and the plant family Fabaceae had the greatest richness of gall morphotypes (16). The plant species Copaifera oblongifolia and Andira humilis (Fabaceae) were the most important host species with five and three morphotypes, respectively. Galling species richness was not affected by none of explanatory variables (plant species richness and abundance of super-host plants). On the other hand, galling species per plant species was negatively affected by plant species richness and positively affected by abundance of super-host plants. This is the first study of arthropod-induced galls conducted in EPA of Rio Pandeiros, Brazil. Our results corroborate previous studies that highlight the importance of super-host plants for galling arthropod diversity on a local scale.